REVISITING THE LEAFLET SECRETORY STRUCTURES IN SUBTRIBE CAJANINAE BENTH. (LEGUMINOSAE, PHASEOLEAE) - Vargas, Wanderleia de [UNESP]; Machado, Silvia Rodrigues [UNESP]; Lewis, Gwilym Peter; Candido, Elisa Silva; Vatanparast, Mohammad; Fortuna-Perez, Ana Paula [UNESP] (Univ Chicago Press, 2018)
Premise of research. Cajaninae is the most speciose subtribe of the legume tribe Phaseoleae, comprising ca. 490 species distributed in 10 genera. The group is characterized by peculiar secretory structures, such as bulbous-based trichomes and vesicular glands. The taxonomic importance of these secretory structures in the tribe Phaseoleae was considered in earlier publications, although few taxa in subtribe Cajaninae were included in those studies. To evaluate the secretory structures on and in the leaflets of representatives of subtribe Cajaninae, anatomical and micromorphological studies were performed. Methodology. Cross sections of the leaflets were studied using LM and SEM, and trichome types were identified for 164 taxa in nine genera of Cajaninae. Pivotal results. A great diversity of trichome forms exists in the studied group, including capitate trichomes, secretory-base trichomes, bulbous-based trichomes, vesicular glands, and secretory idioblasts in the midrib. These are distributed on or in the leaflet blades of 164 taxa in nine genera belonging to Cajaninae and vary in morphology, abundance, and occurrence. For the first time, we describe the glands and idioblasts found within Cajaninae and can confirm that the vesicular glands are the sole type that can be considered as a unifying character of the subtribe. Conclusions. Our findings suggest that caution is needed when interpreting the morphological variation of the types of secretory structures because within the same trichome type there can be different cell numbers and forms. This article expands on earlier findings and revisits in detail gland types reported in previous studies.
Keywords: anatomical traits; Fabaceae; glands; systematics; taxonomy; trichomes